Β2-Adrenergic receptor modulates mitochondrial metabolism and disease progression in recurrent/metastatic HPV(+) HNSCC. (October 2018) - Lucido, Christopher; Callejas-Valera, Juan; Colbert, Paul; Vermeer, Daniel; Miskimins, W.; Spanos, William; Vermeer, Paola
Abstract The incidence of human papillomavirus-associated head and neck squamous cell carcinoma (HPV[ + ] HNSCC) is rapidly increasing. Although clinical management of primary HPV( + ) HNSCC is relatively successful, disease progression, including recurrence and metastasis, is often fatal. Moreover, patients with progressive disease face limited treatment options and significant treatment-associated morbidity. These clinical data highlight the need to identify targetable mechanisms that drive disease progression in HPV( + ) HNSCC to prevent and/or treat progressive disease. Interestingly, β-adrenergic signaling has recently been associated with pro-tumor processes in several disease types. Here we show that an aggressive murine model of recurrent/metastatic HPV( + ) HNSCC upregulates β2 -adrenergic receptor (β2AR) expression, concordant with significantly heightened mitochondrial metabolism, as compared with the parental model from which it spontaneously derived. β-Adrenergic blockade effectively inhibits in vitro proliferation and migratory capacity in this model, effects associated with an attenuation of hyperactive mitochondrial respiration. Importantly, propranolol, a clinically available nonselective β-blocker, significantly slows primary tumor growth, inhibits metastatic development, and shows additive benefit alongside standard-of-care modalities in vivo. Further, via CRISPR/Cas9 technology, we show that the hyperactive mitochondrial metabolic profile and aggressive in vivo phenotype of this recurrent/metastatic model are dependent on β2AR expression. These data implicate β2AR as a modulator of mitochondrial metabolism and disease progression in HPV( + ) HNSCC, and warrant further investigation into the use of β-blockers as low cost, relatively tolerable, complementary treatment options in the clinical management of this disease.